Star wars, the clone wars. The complete season five [videorecording (DVD)] - Lucas, George, 1944-; Kane, Tom, 1962-; Lanter, Matt, 1983-; Taylor, James Arnold, 1969-; Eckstein, Ashley, 1981- ([Publisher not identified], 2013)
The valiant Jedi Knights and clone troopers defend exotic planets from enemy forces. They wage war underwater, battle across a night-shrouded world. The final 23 episodes.